Corporate Responsibility in Money Laundering Crime (Perspective Criminal Law Policy in Crime of Corruption in Indonesia) - Wibowo, Muhtar Hadi (Universitas Negeri Semarang, 2018)
Money laundering is a stand-alone crime, although money laundering is born from its original crime, such as corruption, but the anti-money laundering regime in almost all countries places money laundering as a crime independent of its original crime in the case of a money laundering probe. The purpose of this study is to describe and analyze criminal law policies in regulating corporate accountability for current money laundering, analyze the implementation in law enforcement against corporations engaging in money laundering, and establish a model of criminal law policy on corporate liability that commits a crime money laundering in the future. This research emphasized that criminal law policy in ordering corporate responsibility to money laundering crime has been regulated in Money Laundering Criminal Act. The Money Laundering Act in Indonesia has indeed accepted corporations as a subject of criminal law, there are several cases that indicate the involvement of corporations engaging in money laundering practices in Indonesia but at the stage of settlement within the justice system there is not a single corporation that has been charged and sanctioned criminal. In line with the development of specific laws, corporations are categorized as subjects of criminal law.